Cholesteryl Ester Transfer Protein Polymorphisms, Statin Use, and Their Impact on Cholesterol Levels and Cardiovascular Events. Issue 3 (30th September 2013) - Leusink, M; Onland‐Moret, N C; Asselbergs, F W; Ding, B; Kotti, S; van Zuydam, N R; Papp, A C; Danchin, N; Donnelly, L; Morris, A D; Chasman, D I; Doevendans, P A F M; et al.
<x xml:space="preserve">Abstract</x> The association of nonfunctional variants of the cholesteryl ester transfer protein (CETP) with efficacy of statins has been a subject of debate. We evaluated whether three functional CETP variants influence statin efficacy. The effect of CETP genotype on achieved levels of high‐density lipoprotein cholesterol (HDLc), low‐density lipoprotein cholesterol (LDLc), and total cholesterol during statin treatment was estimated by meta‐analysis of the linear regression outcomes of three studies (11, 021 individuals). The effect of these single‐nucleotide polymorphisms (SNPs) on statin response in protecting against myocardial infarction (MI) was estimated by meta‐analysis of statin × SNP interaction terms from logistic regression in five studies (16, 570 individuals). The enhancer SNP rs3764261 significantly increased HDLc by 0.02 mmol/l per T allele (P = 6 × 10–5) and reduced protection against MI by statins (interaction odds ratio (OR) = 1.19 per T allele; P = 0.04). Focusing on functional CETP variants, we showed that in carriers of the rs3764261 T variant, HDLc increased more during statin treatment, and protection against MI by statins appeared to be reduced as compared with those in noncarriers. Clinical Pharmacology & Therapeutics (2014); 95 3, 314–320. doi:10.1038/clpt.2013.194